Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
### Calculating [tex]\(\left. \frac{d}{dx} \frac{f(x)}{g(x)+2} \right|_{x=1} \)[/tex]
To find the derivative of [tex]\(\frac{f(x)}{g(x)+2}\)[/tex] at [tex]\(x=1\)[/tex], we'll first express the function and then apply the quotient rule.
The quotient rule states that for two differentiable functions [tex]\( u(x) \)[/tex] and [tex]\( v(x) \)[/tex],
[tex]\[ \left( \frac{u(x)}{v(x)} \right)' = \frac{u'(x)v(x) - u(x)v'(x)}{(v(x))^2} \][/tex]
In our case:
- [tex]\( u(x) = f(x) \)[/tex], so [tex]\( u'(x) = f'(x) \)[/tex]
- [tex]\( v(x) = g(x) + 2 \)[/tex], so [tex]\( v'(x) = g'(x) \)[/tex]
### Step-by-Step Calculation:
1. Evaluate [tex]\(u(x)\)[/tex] and [tex]\(v(x)\)[/tex] at [tex]\(x=1\)[/tex]:
[tex]\[ u(1) = f(1) = -1.8 \][/tex]
[tex]\[ v(1) = g(1) + 2 = 6.9 + 2 = 8.9 \][/tex]
2. Evaluate [tex]\(u'(x)\)[/tex] and [tex]\(v'(x)\)[/tex] at [tex]\(x=1\)[/tex]:
[tex]\[ u'(1) = f'(1) = -1.3 \][/tex]
[tex]\[ v'(1) = g'(1) = -2.3 \][/tex]
3. Apply the quotient rule:
[tex]\[ \left( \frac{f(x)}{g(x) + 2} \right)' \Bigg|_{x=1} = \frac{f'(x)(g(x)+2) - f(x)g'(x)}{(g(x)+2)^2} \Bigg|_{x=1} \][/tex]
4. Substituting the values:
[tex]\[ \left( \frac{f(x)}{g(x)+2} \right)' \Bigg|_{x=1} = \frac{-1.3 \cdot 8.9 - (-1.8) \cdot (-2.3)}{8.9^2} \][/tex]
5. Simplify the numerator:
[tex]\[ -1.3 \cdot 8.9 = -11.57 \][/tex]
[tex]\[ -1.8 \cdot -2.3 = 4.14 \][/tex]
[tex]\[ -11.57 - 4.14 = -15.71 \][/tex]
6. Simplify the denominator:
[tex]\[ 8.9^2 = 79.21 \][/tex]
7. Combine to find the derivative:
[tex]\[ \left. \frac{d}{dx} \frac{f(x)}{g(x)+2} \right|_{x=1} = \frac{-15.71}{79.21} \approx -0.1983335437444767 \][/tex]
So the derivative [tex]\(\left. \frac{d}{dx} \frac{f(x)}{g(x)+2} \right|_{x=1}\)[/tex] is approximately [tex]\(-0.1983\)[/tex].
To find the derivative of [tex]\(\frac{f(x)}{g(x)+2}\)[/tex] at [tex]\(x=1\)[/tex], we'll first express the function and then apply the quotient rule.
The quotient rule states that for two differentiable functions [tex]\( u(x) \)[/tex] and [tex]\( v(x) \)[/tex],
[tex]\[ \left( \frac{u(x)}{v(x)} \right)' = \frac{u'(x)v(x) - u(x)v'(x)}{(v(x))^2} \][/tex]
In our case:
- [tex]\( u(x) = f(x) \)[/tex], so [tex]\( u'(x) = f'(x) \)[/tex]
- [tex]\( v(x) = g(x) + 2 \)[/tex], so [tex]\( v'(x) = g'(x) \)[/tex]
### Step-by-Step Calculation:
1. Evaluate [tex]\(u(x)\)[/tex] and [tex]\(v(x)\)[/tex] at [tex]\(x=1\)[/tex]:
[tex]\[ u(1) = f(1) = -1.8 \][/tex]
[tex]\[ v(1) = g(1) + 2 = 6.9 + 2 = 8.9 \][/tex]
2. Evaluate [tex]\(u'(x)\)[/tex] and [tex]\(v'(x)\)[/tex] at [tex]\(x=1\)[/tex]:
[tex]\[ u'(1) = f'(1) = -1.3 \][/tex]
[tex]\[ v'(1) = g'(1) = -2.3 \][/tex]
3. Apply the quotient rule:
[tex]\[ \left( \frac{f(x)}{g(x) + 2} \right)' \Bigg|_{x=1} = \frac{f'(x)(g(x)+2) - f(x)g'(x)}{(g(x)+2)^2} \Bigg|_{x=1} \][/tex]
4. Substituting the values:
[tex]\[ \left( \frac{f(x)}{g(x)+2} \right)' \Bigg|_{x=1} = \frac{-1.3 \cdot 8.9 - (-1.8) \cdot (-2.3)}{8.9^2} \][/tex]
5. Simplify the numerator:
[tex]\[ -1.3 \cdot 8.9 = -11.57 \][/tex]
[tex]\[ -1.8 \cdot -2.3 = 4.14 \][/tex]
[tex]\[ -11.57 - 4.14 = -15.71 \][/tex]
6. Simplify the denominator:
[tex]\[ 8.9^2 = 79.21 \][/tex]
7. Combine to find the derivative:
[tex]\[ \left. \frac{d}{dx} \frac{f(x)}{g(x)+2} \right|_{x=1} = \frac{-15.71}{79.21} \approx -0.1983335437444767 \][/tex]
So the derivative [tex]\(\left. \frac{d}{dx} \frac{f(x)}{g(x)+2} \right|_{x=1}\)[/tex] is approximately [tex]\(-0.1983\)[/tex].
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.